Characterisation and flowability of titanium grade 5 alloy powders - Nziu, P. K. (Vaal University of Technology, 2013)
Flowability is one of the essential physical characteristics considered during the use of any powder in a manufacturing process. However, very little research on flowability of titanium powder has been conducted. To this end, this study dealt with global market survey of titanium powder manufacturers and suppliers. In addition, the effects of various physical parameters such particle size, shape, chemical analysis, density and soundness on flowability of titanium grade 5 alloys powder in additive manufacturing application were investigated. Twelve powder samples of titanium alloy grade 5 (Ti6Al4V) were sourced, tested and analyzed using various methods. The choice of the characterization method used depended on its accuracy, equipment availability and application. Particle size and shape were characterized using laser diffraction and scanning electron microscope techniques, respectively. Quantitative and crystallographic analyses were done to determine the chemical composition as well as alpha and beta phases. Shear cell and dynamic tests were performed to determine bulk density, stability, flow energy and flowability where as particle density was performed by a pcynometer. Research on potential manufacturers was conducted using questionnaires. It was established that high cost of titanium powder is partly driven by titanium powder firms that are not willing to disclose information about the product. It was observed that powder flowability is affected by particle size, shape, chemical composition, density and soundness. The particle density was found to be a function of chemical composition that is the alloying elements and impurities present in the powder. It was noted that bulk density, porosity, cohesion and agglomeration were affected by particle size. Soundness of the powder was also found to improve with sphericity of the particles. Among the physical parameters studied, particle size had the highest effect on powder flowability. The highest flowability was noted at particle size of 41 μm.
M. Tech. (Department of Mechanical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Alloy powders; Flowability of titanium powder; Titanium powder; Titanium alloy grade 5; Dissertations, Academic -- South Africa.; Alloys.; Titanium alloys.